Isolation and characterization of microsatellites loci in Spondias purpurea (Anacardiaceae) and cross amplification in congeneric species - Cristóbal Pérez, Edson Jacob (2019)
Microsatellite markers provide high polymorphism levels, useful to study genetic diversity and gene flow patterns in plant populations. Here we develop and characterize microsatellite primers to evaluate patterns of genetic structure and diversity, and gene flow levels in the dioecious tropical tree Spondias purpurea (Anacardiaceae). Twenty-four microsatellite primers were developed for Spondias purpurea. Polymorphism was evaluated in 139 individuals from three localities in Mexico. Ten loci were polymorphic. The number of alleles ranged between two and 21, the average number of alleles was 5.88. Crossamplification trials on S. mombin, S. radlkoferi, Astronium graveolens and Amphipterygium adstringens achieved successful amplification for only six microsatellites in S. mombin and S. radlkoferi. Microsatellites developed for S. purpurea will be a useful tool to estimate genetic diversity within and among populations, as well as to assess the consequences of habitat fragmentation on gene flow patterns of this species.